FACILITIES OF MEASURING OF WIND FOR RESEARCHES AND PLANNING OF THE AIR FIELDS AND HELIPORTS - Бєлятинський, А.; Угненко, Є.; Панченко, О.; Ульянов, Ю.; Місайлов, В. (Proceedings of National Aviation University, 2012)
The choice of the place for the future airdrome (heliport) construction must satisfy the financial appropriatenessand also exploitation security. For this purpose on the stage of the researches and designing the information is neededabout wind speed and its direction with an error 0,5 m/s and 10 hail accordingly, in a radius up to 15 km, as to heightfrom 2 to 1000 m with resolution 30 m, a spatial interval of measuring in a horizontal plane is not more than 20 km,in time - not rarer, than each 3 hours. Information is needed to be gained for maximal temporal period (it is desirableno less than five years). A device for the receipt of such information must be of low cost. The acoustic andradioacoustic sounding systems answer the indicated requirements most of all